Análisis de costo beneficio a salinas asociados y compañia Zona Limpia período 2009. - Contento Armijos, Ángela Gabriela (2010)
Cost benefit analysis can determine and compare the profitability of a service being offered, minimize costs, optimize the best human and material resources to the administrative work in the advancement of an organization. In this case the analysis Salinas Associates, the same as was done to comply with the general objective is to conduct a Cost Benefit Analysis and Company Associates in Salinas "clean zone" in the province of Loja period 2009. And specific objectives designed to meet the income and expenses that arise within the company, as well as apply the breakeven point for determining the cost benefit of the services offered, all of which were developed based on the theoretical foundations consisting in the literature review. The analysis elaborated mention it to satisfy the following steps: analysis of the costs incurred in 2009, classification of resources in direct and indirect cost sharing of resources by each of the services provided, reporting of costs, determination of the equilibrium with its respective interpretation. Obtained as a result the proposed Benefit to Cost Analysis and Company Associates Salinas "Clean Zone" 2009.la same period that contains the determination of cost in each of the services which can be seen that by applying the formula of the Cost / profit under revenue and total costs of each of the services that presents the car washing area clean, all services in the cost / benefit ratio is greater than one, is there is gain from the service, given that in the Auto Wash has a higher profit margin because in this type of service is the user that performs the washing and the only company that offers cleaning machines, taking a value from its use.